The centrality of the research question for locating PhD studies in the global knowledge society - Simmonds, Shan; du Preez, Petro (South African Journal of Higher Education, 2016)
Although classified as a developing country, South Africa lags far behind other BRICS member countries. A cause for concern is that the number of PhD studies rather than what they contribute is often used to measure their quality. This article argues that a quality PhD study must engage with the global knowledge society. A critical meta-study was conducted to ascertain whether the PhD studies between 2005 and 2012 in South Africa did so. The chief process was the interrogation of the research question in each PhD study, and its links with the topic, the focus and the repositioning of the contribution declared by the study. An analysis of 240 qualitative PhD studies in the education field has revealed that PhD studies with strong internal links tend to have a coherent conceptual build-up and contribute to the global knowledge society. In the conclusion, guidelines for PhD education are presented.